Trade in live reptiles, its impact on wild populations, and the role of the European market. (December 2016) - Auliya, Mark; Altherr, Sandra; Ariano-Sanchez, Daniel; Baard, Ernst H.; Brown, Carl; Brown, Rafe M.; Cantu, Juan-Carlos; Gentile, Gabriele; Gildenhuys, Paul; Henningheim, Evert; Hintzmann, Jürgen; Kanari, Kahoru; et al.
Abstract: Of the 10, 272 currently recognized reptile species, the trade of fewer than 8% are regulated by the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) and the European Wildlife Trade Regulations (EWTR). However, the International Union for Conservation of Nature (IUCN) Red List has assessed 45% of the world's reptile species and determined that at least 1390 species are threatened by "biological resource use". Of these, 355 species are intentionally targeted by collectors, including 194 non-CITES-listed species. Herein we review the global reptile pet trade, its impacts, and its contribution to the over-harvesting of species and populations, in light of current international law. Findings are based on an examination of relevant professional observations, online sources, and literature (e.g., applicable policies, taxonomy [reptile database], trade statistics [EUROSTAT], and conservation status [IUCN Red List]). Case studies are presented from the following countries and regions: Australia, Central America, China, Galapagos Islands (Ecuador), Germany, Europe, India, Indonesia (Kalimantan), Islamic Republic of Iran, Japan, Madagascar, Mexico, New Zealand, the Philippines, South Africa, Sri Lanka, Vietnam, Western Africa, and Western Asia. The European Union (EU) plays a major role in reptile trade. Between 2004 and 2014 (the period under study), the EU member states officially reported the import of 20, 788, 747 live reptiles. This review suggests that illegal trade activities involve species regulated under CITES, as well as species that are not CITES-regulated but nationally protected in their country of origin and often openly offered for sale in the EU. Further, these case studies demonstrate that regulations and enforcement in several countries are inadequate to prevent the overexploitation of species and to halt illegal trade activities. Highlights: A new perspective on global reptile pet trade based on key expert testimony from around the world Many reptile species controlled under current policies remain illegally/unsustainably traded to supply the international reptile pet market, with rare and endemic species most threatened. Monitoring of species and populations in question and the provisioning of scientific knowledge to overcome uncertainties is crucial to prevent over-exploitation. Nationally protected species not regulated within the CITES Appendices cannot be adequately protected from exploitation once illegally removed from their range state.